Conceptualized framework for regulation of OTT video services: A new battlefield of interconnection and peering - Chih-Liang Yeh (International Telecommunications Society (ITS), 2014)
Under the two broad concepts of net neutrality and IP interconnection, it is not easy to distinguish the paid prioritization and paid peering. The prioritized service may be prohibited under a strict net neutrality rule while the paid peering may be a normal arrangement of commercial interconnection. For better service quality, the paid peering replaces the 'best efforts' with 'better than best efforts' which fits customers' desire. In fact, prioritized delivery options for content providers may satisfy specialized requirements in much the same ways as CDNs offer higher QoS and delivery guarantees. In many cases, large content providers build their own CDNs that may also act themselves as normal ISPs by offering terms and conditions that seem equivalent to peering arrangements. The paper also discusses the case of Taiwan authority amending rules to 'regulate' the IP interconnection in order to balance the market power of existing monopolistic operator. Though the measures of reform stop in the consideration whether the rulemaking is adequate or not, the government should carefully review every step it takes to deal with problems of the entire fixed-network market. In conclusion, the paper argues that governments should defer to commercially driven interconnection arrangements and should still be ready to resolve the disputes that become harmful to consumers.
Keywords: 330; IP Interconnection; Paid Peering; Prioritized Services; Content Delivery Network; Net Neutrality; Open Internet